Designing ethical workplaces : the Moldable Model - Dunn, Donald D., (Principles for responsible management education (PRME) collection., 2016)
The unethical behavior of several prominent organizational leaders at the start of this millennium and the subsequent fallout from the media, customers, and employees have brought business ethics to a more prominent place within the vision of company executives. However, the day-to-day tasks of leading an organization and the lack of any research-based knowledge of how to lead and manage company ethics often preempt the opportunity to give priority to ethics at the corporate level. Executive leaders could benefit from a framework with which to evaluate current and to create new corporate ethical management systems (CEMSs). This book offers such a framework called the Moldable Model, a system of consistent components that give busy executives a framework and a guide to build an organization-specific CEMS. This book teaches organizational leaders how to design ethical workplaces utilizing the role modeling, context, and accountability components. In a step-by-step process, the author guides the reader through the research-based components with definitions, ethical leadership theory, research findings, explanations, and the practical application of those components through suggested organizational activities. Readers can expect to develop ethical tools such as a code of ethics, an ethical decision-making ladder, a list of ethical leader attributes, and a complete CEMS for implementation into their specific organizations. Each chapter ends with application exercises, and there are several case studies at the end of the book to aid the reader in the use of these ethical tools. In just a few hours, a busy executive can have the knowledge and tools to design an ethical workplace with the tremendous results discussed in this book.